2010
DOI: 10.1111/j.1095-8649.2010.02606.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive biology of the crocodile shark Pseudocarcharias kamoharai

Abstract: From February 2005 to September 2007, a total of 490 crocodile sharks Pseudocarcharias kamoharai, caught as by-catch in the swordfish and tuna longline fishery that operates in the tropical western Atlantic Ocean, was studied in regard to their reproductive biology. Maximum observed total lengths (L(T)) were 1220 and 1090 mm for females and males respectively, with a high proportion of the catch being composed of mature specimens. Sexual maturity was attained at 760-810 mm L(T) for males (L(T50) = 800 mm) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
54
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(65 citation statements)
references
References 14 publications
(22 reference statements)
5
54
6
Order By: Relevance
“…In this study, most gravid females were also found to have four embryos in uteri but two embryos and three embryos were also found. This was consistent with what Oliveira et al (2010) found in their study. No significant difference in embryo sex ratio from 1:1 was also consistent with that reported in the Atlantic Ocean (Oliveira et al , 2010).…”
Section: Monthly Sample Size Of Females and Males And χ2 For Testingsupporting
confidence: 94%
See 4 more Smart Citations
“…In this study, most gravid females were also found to have four embryos in uteri but two embryos and three embryos were also found. This was consistent with what Oliveira et al (2010) found in their study. No significant difference in embryo sex ratio from 1:1 was also consistent with that reported in the Atlantic Ocean (Oliveira et al , 2010).…”
Section: Monthly Sample Size Of Females and Males And χ2 For Testingsupporting
confidence: 94%
“…The frequency of gravid P. kamoharai was as high as 60%. Oliveira et al (2010) also found that a high proportion of P. kamoharai catch was composed of mature individuals in the Atlantic Ocean. A high proportion of mature and gravid P. kamoharai caught indicates a need for caution as pelagic longline fisheries might greatly influence spawning stock biomass and recruitment of this species.…”
Section: Monthly Sample Size Of Females and Males And χ2 For Testingmentioning
confidence: 78%
See 3 more Smart Citations